HearMeVirtual Reality: Using Virtual Reality to Facilitate Empathy Between Hearing Impaired Children and Their Parents - Embøl, Lasse; Hutters, Carl; Junker, Andreas; Reipur, Daniel; Adjorlu, Ali; Nordahl, Rolf; Serafin, Stefania (Frontiers in Virtual Reality, 2021)
Cochlear implants (CI) enable hearing in individuals with sensorineural hearing loss, albeit with difficulties in speech perception and sound localization. In noisy environments, these difficulties are disproportionately greater for CI users than for children with no reported hearing loss. Parents of children with CIs are motivated to experience what CIs sound like, but options to do so are limited. This study proposes using virtual reality to simulate having CIs in a school setting with two contrasting settings: a noisy playground and a quiet classroom. To investigate differences between hearing conditions, an evaluation utilized a between-subjects design with 15 parents (10 female, 5 male;age M=38.5, SD=6.6) of children with CIs with no reported hearing loss. In the virtual environment, a word recognition and sound localization test using an open-set speech corpus compared differences between simulated unilateral CI, simulated bilateral CI, and normal hearing conditions in both settings. Results of both tests indicate that noise influences word recognition more than it influences sound localization, but ultimately affects both. Furthermore, having simulated bilateral CIs to be equal to or significantly beneficial over having a simulated unilateral CI in both tests. A follow-up qualitative evaluation showed that the simulation enabled users to achieve a better understanding of what it means to be an hearing impared child.